phiD12-Like Livestock-Associated Prophages Are Associated With Novel Subpopulations of Streptococcus agalactiae Infecting Neonates - Renard, Adélaïde; Barbera, Laurie; Courtier-Martinez, Luka; Dos Santos, Sandra; Valentin, Anne-Sophie; Mereghetti, Laurent; Quentin, Roland; van der Mee-Marquet, Nathalie L. (Frontiers in Cellular and Infection Microbiology, 2019)
Group B Streptococcus (GBS) is a major cause of invasive disease in neonates worldwide. Monitoring data have revealed a continuing trend towards an increase in neonatal GBS infections, despite the introduction of preventive measures. We investigated this trend, by performing the first ever characterization of the prophage content for 106 GBS strains causing neonatal infections between 2002 and 2018. We determined whether the genome of each strain harbored prophages, and identified the insertion site of each of the prophages identified. We found that 71.7% of the strains carried at least one prophage, and that prophages genetically similar to livestock-associated phiD12, carrying genes potentially involved in GBS pathogenesis (e.g. genes encoding putative virulence factors and factors involved in biofilm formation, bacterial persistence, or adaptation to challenging environments) predominated. The phiD12-like prophages were (1) associated with CC17 and 1 strains (p=0.002), (2) more frequent among strains recovered during the 2011-2018 period than among those from 2002-2010 (p<0.001), and (3) located at two major insertion sites close to bacterial genes involved in host adaptation and colonization. Our data provide evidence for a recent increase in lysogeny in GBS, characterized by the acquisition, within the genome, of genetic features typical of animal-associated mobile genetic elements by GBS strains causing neonatal infection. We suggest that lysogeny and phiD12-like prophage genetic elements may have conferred an advantage on GBS strains for adaptation to or colonization of the maternal vaginal tract, or for pathogenicity, and that these factors are currently playing a key role in the increasing ability of GBS strains to infect neonates.